Analysis of CD4 and CD8 expression in multidrug-resistant tuberculosis infection with diabetes mellitus: An experimental study in mice. (August 2021) - Agustin, Heidy; Massi, Muhammad Nasrum; Djaharuddin, Irawati; Susanto, Agus Dwi; Islam, Andi Asadul; Hatta, Mochammad; Bukhari, Agussalim; Tabri, Nur Ahmad; Santoso, Arif; Patellongi, Ilhamjaya
Abstract: Background: Tuberculosis (TB) remains a major global health problem, in the top 10 causes of death. As a regulator of the immune response, T-helper (Th) cells activate other lymphocytes from the immune system, such as B cells, to destroy the TB pathogen by releasing CD4 and CD8 Th cells. Diabetes mellitus (DM) is a known cause of developing active pulmonary TB. Few studies have examined the biomolecular expression affecting Mycobacterium tuberculosis (MTB) and multidrug-resistant (MDR) MTB, which are associated with low immunity represented by TB in diabetes and CD4 and CD8 levels. Materials and methods: This animal study used a post-test control group design. We performed an experimental study using 30 BALB/c mice, each weighing 25 g. It included six experimental animal groups, of which three had a diabetes condition induced using intraperitoneal streptozotocin, and all were infected with MTB or MDR TB. We evaluated the CD4 and CD8 levels in each group and analyzed the differences. Results: We found a significant difference in CD4 and CD8 levels in MTB and MDR TB conditions. Conclusion: This study shows that acute infection in experimental mice with MTB and MDR TB with or without diabetes had the highest levels of both CD4 and CD8 cells, which can be a sign of increased cellular immunity in a mice model. Highlights: Tuberculosis (TB) is still a major global health problem. TB with comorbid diabetes mellitus (DM) are associated with increased CD4 and CD8. CD4 and CD8 values are increased in animals with DM plus TB infection.